A HISTORICAL TELEOLOGY IN COLONIAL TAXONOMY OF GIRISH KARNAD’S THE DREAM OF TIPU SULTHAN - KAMALAKKANNAN, K.; GEETHAPRIYA , E. (International Journal of Psychosocial Rehabilitation, 2020)
History has always fascinated Girish Karnad like myth and folklore in his creative imagination .For him history is no longer a static background for a play; rather it is timeless, alive, absurd and mysterious in its entirety. History provides him with the elements of a psychoanalysis, political praxis and revolutionary concepts with a shift from socio-political possibilities to pessimism. By writing historical plays he suspends the disbelief of the audience and readers, and generates a new penchant for the protagonists in it. Rewriting history in the job of a historiographer he rather uncovers and discovers it in the contemporary consciousness. For him history not only appears full of events but also of ethics, discourse, universal law and ideologies as tools to liberate a society or the mankind from slavery, bondage and perils. By projecting the historical personalities and events in his dramatic oeuvres he has expressed his concepts as an objective chronicler and transcendent commentator. In the job of an investigator of a parenthesized period he has discovered the living plasmas of these dead heroes debating over them in painful speculations. Karnad’s historical plays are research oriented both on individual protagonists and on contemporary social, cultural, political and economic conditions of Indian society. Analyzing definite periods in Indian history and the then prevalent situation he gives a detailed picture of the past for its relevance in the present. Karnad never claims as a reformist but his plays on Indian history convey a covert zeal to homogenise the Indian society. His historical plays – Tughlaq, Tale Danda, and The Dream of Tipu Sultan are first written in kannada and then translated and trascreated into English. Although each of these plays deals with different periods of Indian history from twelfth century to nineteenth century an attempt has been made to critique them not in order of the chronology of their composition but in sequence of the incidents and events that they present. Karnad’s The Dream of Tipu Sultan is his third historical play after Tughlaq and Tale Danda based on the historicity of eighth century India. The play exposes the status of Tipu, his psychology, and the stuggle for peace and strategic resistance of this great personality when the princely kingdoms in india were struggling for their individual hegemony, and the British were consolidating their empire. In the dramatization of Tipu’s dreams karnad has projected the historical materials in his conscious endeavor without any prejudices, preoccupations, obsessions and conceived canons. Analysing history in the postcolonial prespectives point of view into the then socio-political paradigms. In the job of historiographer and in the self of a dramatist Karnad has carnivalised the dreams and daunlessness of this great personality in a rhetorical and hypothesizes Tipu from colonial imperatives. Analysing Tipu’s patriotic past and the needs of his present in a rational and realisitic way, Karnad has assessed Tipu ‘s right to self-assertion, war stratagem, desire for his kingdom’s sovereignty, and his diplomacy for trade and peace. At the same time Karnad project Tipu’s personal emotion, love for family and love for his subjects, secular attribute, far-sighted outlook which was akin to the Nehruvian outlook in the twentieth century and dreams for a prospective nationalism in his struggle for freedom from colonial humiliation and exploitation. The play on the one hand projects the imperial victor’s contaminated self that pollutes the ideological pollens of imperial politics and a rhetoric of psychological and emotional duress of Tipu in his existential essentialism on the other.